Predicting Discrimination in L3 Portuguese by Hungarian Speakers: The Effect of Perceptual Overlap - Gabriela Tavares; Andrea Deme; Susana Correia (Languages)
Perceptual overlap has been attested as significantly contributing to difficulties in L2 speech perception. The current study aims at investigating whether this effect is also observable in the context of L3, specifically in the perception of European Portuguese oral vowels by Hungarian listeners. We crossed the results of two experiments—a categorization task and a discrimination task—and found that perceptual overlap is also a significant factor in L3 perception. Furthermore, we compared different measures of perceptual overlap as predictors for discrimination abilities of L3 vowel contrasts. Namely, we compared perceptual overlap scores calculated on group means and scores based on individual results. None of the measures was conclusively more reliable than another in predicting differences in discrimination difficulties. However, accuracy in perception of EP contrasts or vowels absent from the Hungarian vocalic system was significantly lower than for the other vowels, suggesting that non-nativeness can cause difficulties in L3 perception. Additionally, participants who also reported knowledge of German performed more accurately in discrimination of contrasts that included the vowel [ɐ], a vowel absent from their L1 but present in the German vocalic system, indicating a positive effect of knowledge of languages previously acquired on L3 perception.